2002
DOI: 10.1177/0310057x0203000516
|View full text |Cite
|
Sign up to set email alerts
|

The ASA Physical Status Classification: Inter-observer Consistency

Abstract: The American Society of Anesthesiologists (ASA) physical status classification system has previously been shown to be inconsistently applied by anaesthetists. One hundred and sixty questionnaires were sent out to all specialist anaesthetists in Hong Kong. Ten hypothetical patients, identical to those of a similar study undertaken 20 years ago, each with different types and degrees of physical disability were described. Respondents were asked about their country of training and type of anaesthetic practice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(207 citation statements)
references
References 24 publications
2
192
1
12
Order By: Relevance
“…5 The weakness of the ASA score apart from its subjectivity, is its wide inter-observer variability. [4][5][6][7][8] As such, it is hard to use to compare units. The ASA grade has been shown to be a good predictor of post-operative mortality 9 and better in this regard than the Goldman CRIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The weakness of the ASA score apart from its subjectivity, is its wide inter-observer variability. [4][5][6][7][8] As such, it is hard to use to compare units. The ASA grade has been shown to be a good predictor of post-operative mortality 9 and better in this regard than the Goldman CRIA.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] The ASA score has been used to categorise pre-operative risk and is a good indicator of post-operative mortality. 9 It does not, however, provide a quantitative assessment of morbidity and mortality risk and is better at risk stratification.…”
Section: Pre-operative Scoresmentioning
confidence: 99%
“…1,4,9 DISEASES OF THE COLON & RECTUM VOLUME 52: 7 (2009) Nonetheless, a limitation is that allocation of ASA status is prone to interobserver allocation variation, [27][28][29][30] and further, this means that it is potentially prone to allocation bias. Otherwise, it remains a practical and well-established classification tool.…”
Section: Discussionmentioning
confidence: 99%
“…However, older studies showed low consistency (Ͻ60%) in hypothetical patients, 25 and more recent ones show poor interobserver reliability ( ϭ 0.21-0.40). 26 The latter has also never been assessed for endoscopists or endoscopy staff. Differentiating the first 3 grades is especially subjective, so this variable is often dichotomized as III or above in predictor studies.…”
Section: Advantages and Limitations Of Available Comorbidity Indicesmentioning
confidence: 99%